Anxiety, depression and coping strategies among parents of children with autism at zayed higher organization for-people of determination, Abu Dhabi - Odat, Abeer Ali Ahmad Al (2025)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder causing social communication impairments, restricted interests, and repetitive behaviors. A global prevalence of one in every 100 children presents lifelong challenges for affected families. Parents often experience psychological stress due to caregiving issues, inadequate support systems, and societal stigma, especially in Arab countries. This study aims to assess the levels of anxiety, depression, and coping strategies as well as determining factors associated with depression, anxiety, and coping strategies among parents of autism spectrum disorder (ASD) children at the Zayed Higher Organization for People of Determination, Abu Dhabi. This cross-sectional study involved 200 parents of children with autism spectrum disorder (ASD), recruited through convenience sampling. Data was collected by inviting available and willing parents of children with ASD at the Zayed Higher Organization in Abu Dhabi to participate in the study by completing an online self-administered questionnaire. The data was collected using a validated online self-administered questionnaire consisting of the hospital anxiety and depression scale (HADS) to measure anxiety and depression and the Ways of Coping Questionnaire (WOC) to measure coping methods. Data were analyzed using SPSS version 27 with a chi-square test for categorical data. The results show that the majority of the respondents had moderate anxiety levels n=72 (36%) and high depression levels (48.5%), and most of the respondents were moderate-level copers (81.3%). There was no significant association between the respondents' coping levels and their levels of depression and anxiety. The analysis identifies several factors that are significantly associated with anxiety levels: education level (p = 0.011), employment (p = 0.028), marital status (p = 0.022), number of children (p = 0.001), and children’s sex (p = 0.028). In addition to the children age/year (p = 0.010). Depression levels are associated with marital status (p = 0.035) and the children’s method of education (p = 0.002). For coping levels, the factors associated are the respondent's age (p = 0.019), marital status (p = 0.009), and the children’s method of education (p = 0.002). In addition, Income (p = <0.001) and Children age (p = <0.001). In conclusion, understanding the experiences and concerns of parents can guide the provision of services that help parents identify needs related to the challenges of raising children with autism. It suggests that nursing professionals, psychoeducation, collaboration between practitioners and families, and future research should involve a large population and awareness-raising programs. The practical implications of these findings highlight the need for targeted psychological support, counseling services, and family-centered interventions, especially for parents with limited education, low income, and those managing older children. Healthcare professionals, particularly nurses, should be trained to provide culturally sensitive psychoeducation and early emotional support. Workplace flexibility, accessible educational resources for children with ASD, and marital support programs may help improve parental well-being. Future research should involve larger, more diverse populations and support awareness-raising programs at the community and institutional levels